Analisis Dampak Sumber Daya Alam Pasca Penambangan Batu Andesit di Kabupaten Ponorogo Menggunakan Metode Deskriptif - Naufal Syarif Ardyanto; Ivan Ardiansyah; Tuhu Agung Rachmanto (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
This research was conducted at an andesite mining industry company in Ponorogo district. This research is based on the mining industry in Indonesia which is very developed and also produces a large impact. The aim of this research is that we can find out the impacts produced by the andesite mining industry. This research uses qualitative methods so that it can be seen before the forest is mined and after the forest is mined. This research produces impact analysis data produced by the andesite mining industry, namely a decrease in air quality, water quality, soil quality and increased noise due to mobilization and mining equipment.